2014
DOI: 10.1177/1074248414545127
|View full text |Cite
|
Sign up to set email alerts
|

Looking into the Crystal Ball—Upcoming Drugs for Dyslipidemia

Abstract: Dyslipidaemia is a critical risk factor for the development of cardiovascular complications such as ischemic heart disease and stroke. Although statins are effective anti-dyslipidemic drugs, their usage is fraught with issues such as failure of adequate lipid control in 30% of cases and intolerance in select patients. The limited potential of other alternatives such as fibrates, bile acid sequestrants and niacin has spurred the search for novel drug molecules with better efficacy and safety. CETP inhibitors su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Severe and resistant cases are treated with LDL apheresis in combination with drug therapy. Also, new therapy such as PSCK9 inhibitors, mipomersen, and finally the lomitapide may help these patients in the future [21]. This review is focused on lomitapide treatment and particularly presents the original findings.…”
Section: Management Of Homozygous Familial Hypercholesterolemiamentioning
confidence: 99%
“…Severe and resistant cases are treated with LDL apheresis in combination with drug therapy. Also, new therapy such as PSCK9 inhibitors, mipomersen, and finally the lomitapide may help these patients in the future [21]. This review is focused on lomitapide treatment and particularly presents the original findings.…”
Section: Management Of Homozygous Familial Hypercholesterolemiamentioning
confidence: 99%
“…3,35 and lomitapide (a microsomal transfer protein inhibitor) (Juxtapid-Aegerion). 39 These agents interfere with the production and secretion of apoB-containing lipoproteins respectively, independent of the LDL receptor. These agents are used after statins, cholesterol absorption inhibitors and bile acid sequestrants have been considered.…”
Section: Niacinmentioning
confidence: 99%
“…In addition, statins also increase the expression of low-density lipoprotein receptor (LDLR) on the cell surface, which induces the clearance of LDL-C from the bloodstream [ 5 ]. However, failure to reach normal levels of cholesterol (despite patients consuming the maximum dosage of statins) and non-compliance due to potential adverse side effects (such as musculoskeletal disorders, abdominal pain, headaches, numbness, and skin rashes) are two primary causes for the discontinuation of statin therapy in some patients, which has raised debate regarding the potential risks and benefits of statin therapy [ 6 , 7 , 8 , 9 , 10 ]. It has also been reported that statins may induce oxidative stress in patients with chronic heart failure, diabetes, and myopathy, as statin drugs interfere with the synthesis of coenzyme Q10 [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%